Pengaruh Sistem Insentif terhadap Perilaku Manajerial: Studi Empiris dalam Akuntansi Keperilakuan - Abdurrohim Abdurrohim; Tri Candra Anggraini; Ratih Kusumastuti (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research analyzes the impact of incentive systems on managerial behavior in the realm of behavioral accounting. Using empirical methods, we collected data from a number of managers across various industrial sectors. Data analysis examined the significant relationship between incentive systems as independent variables and managerial behavior as dependent variables. The research results indicate that incentive systems have a significant influence on managerial behavior. These findings validate the hypothesis that the design of incentive systems can affect how managers act in the context of accounting. The practical implications of this research encourage a deeper understanding of incentive structures that can motivate desired managerial behavior. As a contribution to behavioral accounting theory, this research also provides valuable insights for practitioners in designing effective incentive systems that are contextually appropriate.